The relationships of serum vitamin D concentration with linear speed and change of direction performance in soccer players - Michalczyk, M. M.; Kałuża, M.; Zydek, G.; Roczniok, R.; Golas, A. (Frontiers in Nutrition, 2024)
The aim of the study was to establish whether the level of 25 hydroxyvitamin D (25(OH)D) in serum has an influence on speed (m/s) and change of direction (COD, s) performance. Twenty male soccer players from the top league participated in the study. All subjects were evaluated for the serum concentration of 25(OH)D at the beginning of the preseason. The linear sprint test was performed at 5 m and 30 m, and COD (time and deficit) at the beginning (BPP) and after (APP) 6 weeks of the preparatory period. The results revealed that 20% of soccer players had a significant deficiency of 25(OH)D (<20 ng/mL) and 30% had insufficient 25(OH)D levels (between 20 and 30 ng/mL). Positive correlations were found between the training effect for the ∆COD (BPP-APP) (p = 0.003) and ∆deficit (BPP-APP) (p = 0.039). Significant differences were noticed for the ∆COD (m = 0.60 [s]) and ∆deficit (m = 0.56[s]) in the soccer players whose 25(OH)D concentration was <=30 ng/mL, and for the ∆COD (p = 0.002) and ∆deficit (p = 0.017) in the soccer players whose 25(OH)D concentration was >30 ng/mL. The training effect was significantly higher for the soccer players whose 25(OH)D concentration was above 30 ng/mL. Soccer players with higher 25(OH)D levels achieved superior results in the COD test and demonstrated better deficit outcomes, affirming the positive influence of 25(OH)D on muscle metabolism.